Evaluation of plant extracts against Rhizoctonia solani causing sheath blight of rice (The Journal of Plant Protection Sciences, 2020)
The antifungal effect of 44 plant extracts and 8 plant oils against the pathogen Rhizoctonia solani was evaluated by disc diffusion method. Out of 44 plants tested, 36 plant extracts showed varied degree of antimicrobial effect at different concentrations against the pathogen whereas 8 plant extracts, viz. Abrus precatorious, Acacia auriculiformis, Bougainvillea glabra, Convolvulus arvensis, Hibiscus
Keywords: Rice; Rhizoctonia solani; Sheath blight; plant extracts; plant oils; disc diffusion method; fungitoxicity